Some features of Mn²⁺ EPR spectra in cubic nano-ZnS - Vorona, I.P.; Ishchenko, S.S.; Okulov, S.M.; Nosenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
Four ZnS nanopowders containing an uncontrolled impurity of manganese were studied using the EPR technique. The powders with the average sizes (6…8 nm) were synthesized by either joint or sequential decomposition of diethyldithiocarbamate complexes of zinc and europium in high-boiling solvents at various temperatures. All samples demonstrated the EPR signal that is not typical for ZnS powders with µm-sized particles. Computer simulation showed that the EPR spectra of all the samples could be fitted by two components. The first component with g = 2.0022 ± 0.0002, = (−63.5±0.5)·10⁻⁴cm⁻¹, ⁰₄ ≥ 3.5·10⁻⁴cm⁻¹ was assigned to Mn²⁺ ions in the cubic surrounding, Mn(C). The parameters of the second component were g = 2.0022 ± 0.0002, = (−63.5±0.5)·10⁻⁴cm⁻¹, ⁰₂ = (−36±1)·10⁻⁴cm⁻¹; this component was attributed to Mn²⁺ ions associated with a planar lattice defect (stacking fault), Mn²⁺(D). The ratio of center amounts Mn²⁺(C)/Mn²⁺(D) for the samples studied was 2.1/1 (in the samples 1 and 4) and 1.7/1 (in the samples 2 and 3), respectively. EPR of Mn²⁺ ions was shown to be an effective method for detecting planar lattice defects in ZnS nanoparticles.